2016
DOI: 10.1002/2015jc011156
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of future increased Arctic runoff on Arctic Ocean stratification, circulation, and sea ice cover

Abstract: The Arctic Ocean has important freshwater sources including river runoff, low evaporation, and exchange with the Pacific Ocean. In the future, we expect even larger freshwater input as the global hydrological cycle accelerates, increasing high‐latitude precipitation, and river runoff. Previous modeling studies show some robust responses to high‐latitude freshwater perturbations, including a strengthening of Arctic stratification and a weakening of the large‐scale ocean circulation; some idealized modeling stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
104
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(123 citation statements)
references
References 72 publications
5
104
1
Order By: Relevance
“…An impulsive increase in the HF through the Fram Strait leads to an increase in the HC of the BG after a decade or so but has no discernible effect on the other metrics under consideration. Some of our results can be compared with findings of Nummelin et al (2015Nummelin et al ( , 2016 and Pemberton and Nilsson (2016), who studied the impact of river discharge on the Arctic Ocean. These studies assumed that future Arctic river runoff will likely increase due to intensification of the global hydrological cycle.…”
Section: Climate Response Functionsmentioning
confidence: 67%
See 1 more Smart Citation
“…An impulsive increase in the HF through the Fram Strait leads to an increase in the HC of the BG after a decade or so but has no discernible effect on the other metrics under consideration. Some of our results can be compared with findings of Nummelin et al (2015Nummelin et al ( , 2016 and Pemberton and Nilsson (2016), who studied the impact of river discharge on the Arctic Ocean. These studies assumed that future Arctic river runoff will likely increase due to intensification of the global hydrological cycle.…”
Section: Climate Response Functionsmentioning
confidence: 67%
“…Thus, understanding the response to river runoff (especially as the climate warms and the hydrological cycle intensifies) is important for predicting future change. Numelinn et al (2016) and Pemberton and Nilsson (2016), for example, have found that increased river runoff leads to a strengthening of the central Arctic Ocean stratification and a warming of the halocline and Atlantic Water layers. Further, excess freshwater accumulates in the Eurasian Basin, resulting in local sea-level rise and a reduction of water exchange between the Arctic Ocean and the North Pacific and North Atlantic Oceans.…”
Section: Forcing Functionsmentioning
confidence: 99%
“…Nutrient limitation may become more widespread in a changed Arctic Ocean as freshening from increased river runoff and ice melt (Morison et al 2012) suppresses vertical mixing (Nummelin et al 2016) and reduce light availability due to increased turbidity. This could potentially lead to reduced primary production in surface waters.…”
Section: Marine Carbon Cyclingmentioning
confidence: 99%
“…The relation between the amplified moisture transport toward norther latitudes and its influence on river discharge was demonstrated by Zhang et al [32]. Several authors have discussed the recent increase in river discharge over the Arctic (e.g., [33,34]), and it was determined that the river discharge has an influence over the Arctic system in different ways [24]. Although its influence on sea ice extent remains unclear, several studies have suggested a link between river runoff and summer ice melt or early freezing [25,26,35].…”
Section: Introductionmentioning
confidence: 99%
“…The recent change in the perennial sea ice [22,23] is considered one of the most important reasons for the decrease in sea ice volume by several authors. However, variations in the hydrological cycle can affect sea ice too, and in some reports the reduction in sea ice has been related to increased river discharge [24][25][26] or storm activity [27,28]. Atmospheric moisture transport has an important role in sea ice extent variations.…”
Section: Introductionmentioning
confidence: 99%